Intrinsic and extrinsic factors combine to affect baboon movements across natural and urban environments - Anna Bracken (Animal Behaviour, 2024)
Wildlife movement in urban environments can differ significantly from that in natural environments due to intrinsic factors (individual phenotype) as well as extrinsic factors (such as changes to the landscape and increased interactions with people). Here, we used tracking collars equipped with 1 Hz GPS to investigate the variation in fine-scale movement (individual step lengths, path tortuosity and residence times) of chacma baboons, Papio ursinus, across natural and urban environments in Cape Town, South Africa. We showed that the baboons exhibited limited interindividual differences in average movement (intrinsic factor: behavioural type), but large differences across environment (extrinsic factor: behavioural plasticity), where all baboons travelled faster and straighter, and spent less time in one location, when in urban space compared to natural space. We showed large intraindividual differences in baboon movement (behavioural predictability), indicating that some individuals exhibit greater consistency in movement than others. Finally, we showed an interaction between individual (ID) and environment (urban) for all metrics, where individuals differed in how much their movement in urban space changed compared to their movement in natural space. The individuals that changed their movement the most tended to be higher-ranking, socially connected baboons, which are the focus of the city’s baboon management programme, seeking to keep baboons out of urban areas. We therefore suspect these changes in movement between natural and urban space to be partly a result of human–baboon interactions. Taken together, our results show how individual animal movement can be impacted by changing environments, affecting certain baboon phenotypes more than others.